Pengaruh Pembelajaran Daring (BDR) Terhadap Perkembangan Sosial Anak Pada Masa Pandemi DI Taman Kanak-kanak - Nela Yunita; Dadan Surayana (Jurnal Family Education, 2021)
This study aims to examine the effect of BDR online learning on the social development of children at the Bunga Harapan Bunga Pasang Kindergarten. This type of research is a quantitative study using a questionnaire distributed to parents/guardians of students. The population in this study were children and their parents in the beam center group of 8 people, the imtaq center 8 people and the arts center 8 people. So the number of samples used is as many as 24 parents / guardians of students. The data collection technique is a questionnaire. The data analysis technique used the formula Ttable and Fcount which was analyzed using IMB SPSS 26. Based on the data analysis, the coefficient of determination of online learning bdr on social development hypotheses Tcount>Table (2,497>1,711) and Fcount>Ftable (6,253> 1,711). This means that there is a significant effect of BDR learning on the social development of children at the Bunga Harapan Bunga Pasang Kindergarten